2018
DOI: 10.1093/sleep/zsy221
|View full text |Cite
|
Sign up to set email alerts
|

Are U.S. adults reporting less sleep?: Findings from sleep duration trends in the National Health Interview Survey, 2004–2017

Abstract: Study Objectives To document trends in self-reported sleep duration for the noninstitutionalized U.S. civilian population from 2004 to 2017 and examine how sleep trends vary by race/ethnicity. Methods We use data from the National Health Interview Survey (NHIS) for U.S. noninstitutionalized adults aged 18–84 from 2004 to 2017 (N = 398 382). NHIS respondents were asked how much they slept in a 24-hour period on average, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
107
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(124 citation statements)
references
References 55 publications
6
107
1
2
Order By: Relevance
“…In recent decades, an additional lifestyle risk factor has become common in modern society: circadian disruption. Notably, approximately 20% of individuals are involved in shift work [3], 33% sleep no more than 6 h per night [4] and 69% experience social jet lag [5]. Accumulating epidemiological studies have demonstrated significant associations between circadian disruption-related lifestyles and an increased risk of type 2 diabetes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, an additional lifestyle risk factor has become common in modern society: circadian disruption. Notably, approximately 20% of individuals are involved in shift work [3], 33% sleep no more than 6 h per night [4] and 69% experience social jet lag [5]. Accumulating epidemiological studies have demonstrated significant associations between circadian disruption-related lifestyles and an increased risk of type 2 diabetes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Deficient sleep has been associated with leading causes of death in the United States, including cardiovascular disease, malignant neoplasms, cerebrovascular disease, work accidents, diabetes, and hypertension, among others [10,11]. Despite the crucial role that sleep plays in our health, a recent study of nearly 400,000 respondents revealed that Americans are sleeping less than they did a decade ago; in 2017, 32.9% of Americans were sleeping six hours or fewer, compared to 28.6% in 2004 [12]. Considering the essential role of daylight on circadian rhythm, there is strong evidence linking daylight to sleep and general health indicators.…”
Section: Introductionmentioning
confidence: 99%
“…55 A recent study of US adults also found that the prevalence of short sleep duration increased and racial disparities in short sleep widened between 2013 and 2017. 56 Moreover, even if parenting behaviors regarding the bedtimes of young children have remained stable over time, normative behaviors of children immediately preceding bedtime (e.g., exposure to blue light via various screen technologies) may have changed in ways that are detrimental to sleep quality. 57 Should contemporary, nationally representative bedtime data among kindergarteners become available in the future, we encourage researchers to replicate and extend our study to address these potential issues.…”
Section: Discussionmentioning
confidence: 99%